The crochet stitch dictionary : 440 patterns for textures, shells, bobbles, lace, cables, chevrons, edgings, granny squares, and more /: 440 patterns for textures, shells, bobbles, lace, cables, chevrons, edgings, granny squares, and more. (2021) - Braas, Nele; Hetty-Burkart, Eveline
No abstract available